Direct and residual effect of integrated micronutrient application in soybean (Glycine max)-wheat (Triticum aestivum) cropping system - Billore, S D; Joshi, O P (The Indian Journal of Agricultural Sciences, 2005)
A field experiment was conducted during 1997-2000 to study direct and residual effect of integrated micronutrient application on soybean [Glycine may (L.) Merr.]-wheat (Triticum aestivum L. emend. Fiori & Paol.) cropping system. The results show that application of farmyard manure @ 10 tonnes/ha applied in rainy season (kharif was found superior in total productivity of the system which was further confirmed by the highest values (0.82) of sustainable yield index. Stability analysis indicated that application of Zn @ 5 kg/ha to soybean (0.99), farmyard manure @ 10 tonnes/ha (0.92) and their integration (1.06) gave stable production over the years, while boron @ 0.5 kg + farmyard manure, Zn @ 5 kg + boron @ 0.5 kg/ha and seed treatment with sodium molybdate @ 4 g/kg seed showed stable performance under favourable environments. The seed treatment with sodium molybdate @ 4 g/kg seed was found most remunerative in soybean-wheat cropping system.